2007
DOI: 10.1111/j.1600-0714.2007.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibodies against p63 and p73 isoforms in sera from patients diagnosed with oral lichen planus

Abstract: This is the first demonstration of antibodies directed against all p63 and some p73 isoforms in sera from patients diagnosed with OLP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 24 publications
1
48
1
Order By: Relevance
“…25,26 The antigen was originally believed to be specific for CUS, but a report by Ebrahimi et al has shown that it can also be found in OLP. 27 The tremendous overlap between CUS and erosive OLP likely is the reason why many CUS cases may have gone undiagnosed and helps explain the low number of CUS cases reported in the literature. 3 The theory that CUS is a subset of OLP makes some sense, given the histopathologic similarities, but there has been no strong evidence to support this hypothesis in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…25,26 The antigen was originally believed to be specific for CUS, but a report by Ebrahimi et al has shown that it can also be found in OLP. 27 The tremendous overlap between CUS and erosive OLP likely is the reason why many CUS cases may have gone undiagnosed and helps explain the low number of CUS cases reported in the literature. 3 The theory that CUS is a subset of OLP makes some sense, given the histopathologic similarities, but there has been no strong evidence to support this hypothesis in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…Still, there is no consensus as to whether or not it is a systemic disease. Neither is the cause of this disease known, even if autoimmunity has been discussed, potentially caused by disturbances in differentiation of the keratinocytes (3,17). In order to gain more insight into these issues, we performed whole genome expression analysis concentrating on the epithelium only.…”
Section: Discussionmentioning
confidence: 99%
“…This tissue pattern has been associated with the presence of circulating antibodies that stain the nuclei of epithelial cells on monkey esophagus by indirect IF and that recognize a 70‐kDa antigen, a member of the tumor suppressor gene p53 family . The oncogenic role of this humoral response against p53 protein isoforms – the genes of which are mutated in more than 50% of human cancers – with regard to the development of oral cancer in patients with oral LP has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Autoantibodies against type XVII collagen have been occasionally reported in mucosal LP, especially in patients with vulvar involvement . Autoantibodies with different specificities have also been described, namely against BP230 and different isoforms of the tumor suppressor gene p53 family proteins, including the chronic ulcerative stomatitis antigen of 70‐kDa.…”
Section: Introductionmentioning
confidence: 99%